1997
DOI: 10.1097/00005768-199711000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-specific creatine kinase gene polymorphisms in elite endurance athletes and sedentary controls

Abstract: The purpose of this study was to investigate the association between elite endurance athlete (EEA) status and two restriction fragment length polymorphisms (RFLPs) at the muscle-specific creatine kinase (CKMM) gene locus. Genomic DNA was extracted from white blood cells or lymphoblastoid cell lines of 124 unrelated Caucasian male EEA (VO2max > 73 mL.kg-1.min-1) and 115 unrelated Caucasian sedentary male controls (SCON). The genetic polymorphism at the CKMM locus was detected by the polymerase chain reaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 16 publications
4
46
1
Order By: Relevance
“…Identification of alleles Hp *1F , Hp *1S , and Hp *2 was based on product analysis of three independent PCR. MnSOD, CAT, GPx-1, CK-MM, CRP, and MTHFR genotypes were determined by polymerase chain reaction (PCR)-based restriction fragment length polymorphism (RFLP) assays performed as described by Mitrunen et al [94] (MnSOD), Ukkola et al [134] (CAT), Zhao et al [147] (GPx-1), Rivera et al [113], Zhou et al [148,149] (CK), Suk et al [127] (CRP), and Yi et al [145] (MTHFR). DNA fragments containing I/D polymorphism in intron 16 of the ACE gene were amplified by PCR as previously described by Rigat et al [112], using DMSO (dimethyl sulfoxide) as recommended by Odawara et al [100], to avoid mistyping of the DD genotype.…”
Section: Biochemical Analyses and Cell Countsmentioning
confidence: 99%
“…Identification of alleles Hp *1F , Hp *1S , and Hp *2 was based on product analysis of three independent PCR. MnSOD, CAT, GPx-1, CK-MM, CRP, and MTHFR genotypes were determined by polymerase chain reaction (PCR)-based restriction fragment length polymorphism (RFLP) assays performed as described by Mitrunen et al [94] (MnSOD), Ukkola et al [134] (CAT), Zhao et al [147] (GPx-1), Rivera et al [113], Zhou et al [148,149] (CK), Suk et al [127] (CRP), and Yi et al [145] (MTHFR). DNA fragments containing I/D polymorphism in intron 16 of the ACE gene were amplified by PCR as previously described by Rigat et al [112], using DMSO (dimethyl sulfoxide) as recommended by Odawara et al [100], to avoid mistyping of the DD genotype.…”
Section: Biochemical Analyses and Cell Countsmentioning
confidence: 99%
“…Although numerous studies have reported a relationship between these two items [9][10][11][12][13][14], it remains controversial. Furthermore, mitochondrial DNA (mtDNA) [15,16], the creatine kinase gene [17][18][19] and the Na ϩ -K ϩ -ATPase ∂2 gene [20] have been studied as genes that may dictate individual differences in endurance capacity or trainability. mtDNA is a double-stranded, circular molecule of 16,569 bp within the mitochondria [21] and has many more polymorphisms than seen in nuclear DNA [22].…”
mentioning
confidence: 99%
“…Particularly, genetic factors differ mainly because of the diversity of genes possessed by individuals. In recent years, several papers investigated the related genes to the individual difference in the effects of endurance training [5][6][7][8][9][10]. Previous studies have reported mitochondrial DNA (mtDNA) [5,7] 563…”
mentioning
confidence: 99%
“…[8], and creatine kinase genes [9,10] as candidate genes involved in the individual differences in endurance capacity (ex., VO 2 max ) as well as its trainability (ex., the change of VO 2 max ) of endurance training.…”
mentioning
confidence: 99%